ISOLASI JENIS ASAM LEMAK DARI BERBAGAI BAHAN BAKU : ARTIKEL REVIEW - Oktavia Rajebi; Adinda Putri Sabrina; Farida Nur Aeni; Aghnia Ahda; Neni Sri Gunarti (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2023)
Fats or triglycerides are compounds derived from glycerin with three fatty acids, which in the intestine are hydrolyzed into their components. Fatty acids can be obtained from various sources, both animal and vegetable. Fatty acids derived from animal fats are unsaturated fatty acids contained in fish oil. Fatty acids derived from several types of vegetable oils, such as palm oil and cocoa butter, contain saturated fatty acids consisting of palmitic acid (C16H31COOH) and stearic acid (C17H35COOH). Obtaining fatty acids can be conducted by the isolation method, so that the type of fatty acids contained in a sample can be determined, the purpose of this study is to determine the types of fatty acids isolated from various sources of raw materials using the literature review study method. The results of various studies show that fatty acids can be obtained from various natural materials such as animal and vegetable products, including oil palm skin, shark liver oil, catfish oil, wet and dry Moringa seeds, nutmeg seed oil, melinjo fruit seeds, marine yeast oleaginous, olive oil, and fusarium verticilloides species. The types of fatty acids obtained were oleic acid, palmitic fatty acid, DHA, omega 3 and omega 6, trimyristin fatty acid, isanic acid, linoleic acid, stearic acid, palmitoleic acid. So that by isolating the sample, it can be known the type of fatty acids contained in it, both from animals and plants.